The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1038/sj.jea.7500264
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of chronic exposure to cigarette smoke and its change during pregnancy by segmental analysis of maternal hair nicotine

Abstract: This study aimed to investigate the association between biomarkers of fetal exposure to smoking during the whole pregnancy, nicotine in maternal and newborns hair samples, and quantitative measurement of smoking intake and exposure evaluated by maternal self-reported questionnaire. Study subjects were 150 mothers and their newborns from a hospital in Barcelona. A questionnaire including smoking habits was completed in the third trimester of pregnancy and on the day of delivery. Nicotine content was measured in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
43
0
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 25 publications
4
43
0
4
Order By: Relevance
“…In the present study, we observed a mean decrease in nicotine levels from 15.6 ng/mg of hair in the first trimester to 10.1 ng/mg hair in the third trimester, without any reported reduction in smoking. Pichini et al have also reported lower nicotine levels in hair during late pregnancy [28]. This apparent acceleration in nicotine metabolism during pregnancy may be the result of the 50% pregnancy induced increased hepatic blood flow or an increased enzyme induction during gestation.…”
Section: Discussionmentioning
confidence: 91%
“…In the present study, we observed a mean decrease in nicotine levels from 15.6 ng/mg of hair in the first trimester to 10.1 ng/mg hair in the third trimester, without any reported reduction in smoking. Pichini et al have also reported lower nicotine levels in hair during late pregnancy [28]. This apparent acceleration in nicotine metabolism during pregnancy may be the result of the 50% pregnancy induced increased hepatic blood flow or an increased enzyme induction during gestation.…”
Section: Discussionmentioning
confidence: 91%
“…Nicotine can also be measured in hair, and this depot may be useful for assessment of exposure over longer periods (Al-Delaimy, 2002). Pichini et al (2003) measured nicotine in different segments of hair from pregnant women and found this to provide a useful assessment of levels of exposure to tobacco smoke at different times during pregnancy.…”
Section: Measures Of Tobacco Exposurementioning
confidence: 99%
“…A questionnaire that included years of tobacco smoking, average number of daily smoked cigarettes and their brand, and presence of other smokers in the household was administered. From information of the questionnaire, nicotine daily intake (average number of cigarettes smoked per day multiplied by nicotine content in mg of each cigarette) was calculated (11,14). None of the woman declared the use of tobacco products other than cigarettes or consumption of illicit substances during pregnancy.…”
Section: Participantsmentioning
confidence: 99%
“…On the other hand, it has recently been shown that nicotine in different segmental of maternal hair is an adequate biomarker of chronic exposure to cigarette smoking during pregnancy, which fairly correlates with acute exposure measured by urinary cotinine concentration in the newborn (13)(14)(15).…”
mentioning
confidence: 99%
See 1 more Smart Citation